For Better and for Worse - How Unpaid Bride Wealth provides Security - Hans Hoogeveen (Tinbergen Institute, 2000)
The obligation to pay bride wealth at marriage is usually associated with thecontinuation of the lineage or considered a compensation for the loss of laborfor the family that provides the bride. In this paper a different interpretationis advanced. The obligation to pay of bride wealth is seen as informal insurancewhich relies on the fact that bride wealth liabilities are contingent claims.Empirical evidence from Zimbabwe is presented to support this claim. In theabsence of formal insurance mechanisms, bride wealth qualifies as an importantsecurity enhancing institution: the arrangement covers nearly the completeZimbabwean adult population and permits to pool risks between many differentfamilies. Additionally the amounts involved are large and the period of timeduring which the claims provide security long. Like any informal insurancearrangement, the marriage system is prone to failure as a result of covariantrisk and information and enforcement problems. It is shown how the marriageprocedure deals with these problems.
Keywords: G21; O17; Q14; 330; Risk; Insurance; Institutions; Bride Wealth; Africa; Familienökonomik; Afrika